Sustainable Tourism Communication Strategy In Pampang Cultural Village, Samarinda, East Kalimantan - Paramita, Sinta; Kahumako, Agustina; Irawan, Agustinus Purna (Universitas Brawijaya, 2025)
Sustainable tourism communication strategies are a crucial approach to developing tourist destinations, addressing not only economic aspects but also social and environmental aspects. Appropriate tourism communication strategies, such as effective information dissemination, strengthening the destination's image, community participation, interactive communication with tourists, and ongoing education for local communities, are integral to sustainable tourism development. Pampang Cultural Village, located in Balikpapan, East Kalimantan, is rich in local traditions and culture and serves as an ideal example for implementing sustainable tourism communication. This study aims to analyze the communication strategies used by village managers to promote sustainable tourism and their impact on the local community and the environment. A case study method and a qualitative approach, including in-depth interviews and participant observation, will be used in this study. This study analyzes sustainable tourism communication strategies at Pampang Cultural Village and finds that a holistic, integrated approach is key to sustainability. The four main components of the education and empowerment community program development (CBT), stakeholder engagement, and the use of digital technology work synergistically. Education builds awareness, CBT empowers local communities, stakeholder synergy creates a harmonious ecosystem, and digital technology expands the reach of promotions. Integrating these four elements into a cohesive narrative is crucial. As a result, Pampang Cultural Village has the potential to become a sustainable destination that preserves culture and has a positive impact on the community and the environment